Tevriyedeki İham - Saraç, M. A. Yekta (Kitabevi, 2002)
This essay claims that literary figures "tevriye" and "iham" have basically the same meaning and function in poetry. However, recently it has been argued that these two figures have different semantic and rhetorical natures, because while carrying various meanings in itself at the same time, "iham" stands towards the aimed meaning in an equal distance among other meanings. This article isarguing the problem under traditional understandings of rhetoric.
"lham" in "Tevriye"
Keywords: İham (Deception in Multi-Meanings); Tevriye (Double-Entendre); Rhetoric; Tevcih (Aiming Multi-Meanings); İstihdam (Meaning Connotations)